2019
DOI: 10.1016/j.neuropharm.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor signaling mitigates the impact of acute social stress

Abstract: Brain-derived neurotrophic factor (BDNF) is known to promote fear learning as well as avoidant behavioral responses to chronic social defeat stress, but, conversely, this peptide can also have antidepressant effects and can reduce depressant-like symptoms such as social avoidance. The purpose of this study was to use a variety of approaches to determine whether BDNF acting on tropomyosin receptor kinase B (TrkB) promotes or prevents avoidant phenotypes in hamsters and mice that have experienced acute social de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 107 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…BDNF is a member of the neurotrophin family of growth factors, which is involved in neuronal homeostasis and brain plasticity‐related process 40 . A previous study put forward that BDNF–TrkB signaling reduced anxiety‐ and depression‐like symptoms following short‐term social stress 41 . Another study reported that SIRT1 activation could ameliorate spatial memory deficits by altering hippocampal BDNF–TrkB signaling 42 .…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a member of the neurotrophin family of growth factors, which is involved in neuronal homeostasis and brain plasticity‐related process 40 . A previous study put forward that BDNF–TrkB signaling reduced anxiety‐ and depression‐like symptoms following short‐term social stress 41 . Another study reported that SIRT1 activation could ameliorate spatial memory deficits by altering hippocampal BDNF–TrkB signaling 42 .…”
Section: Discussionmentioning
confidence: 99%
“…This further supports the BDNF stress-sensitivity hypothesis that BDNF dysregulation, as with the Val66Met polymorphism, predicts vulnerability to stress [ 217 ]. Indeed, TrkB receptor blockade enhances defeat-induced avoidance and PTSD-like symptoms in models of acute social and single-prolonged stress, which were mitigated by TrkB activation [ 218 , 219 ]. It should be stressed that secondary modulation of dopaminergic and serotonergic transmission by BDNF represents one mechanism affecting anxiety, depression, and schizophrenia as previously described mechanisms such as neuroinflammation, oxidative stress, and plasticity impairments are also involved and modulated by BDNF.…”
Section: Therapeutic Bdnf Mechanismsmentioning
confidence: 99%
“…Similar delayed effects are also reported after exposure to other types of acute stressors including acute predator stress and one‐time injection of the stress hormone corticosterone (Cohen et al, 2006; Kim et al, 2014, 2015; Zohar et al, 2008) and can be detected even 30 days afterwards (Kozlovsky, Matar, Kaplan, Kotler, Zohar, & Cohen, 2007). Rodents also show enhanced social anxiety (a symptom often reported in PTSD patients; Collimore et al, 2010) which is quantified by a decrease in social interaction of a stressed animal with an unfamiliar conspecific (Chakraborty et al, 2020; Lehmann et al, 2016; Rosenhauer et al, 2019; Saxena et al, 2020; Varlinskaya & Spear, 2008) (Table 1). So while stress does alter salience processing of both social and non‐social cues, could social and asocial anxiety divergently evolve over time after the same stressful experience?…”
Section: Stress Effects On Behaviour: the ‘What’ And The ‘When’mentioning
confidence: 99%